Exploring violin students’ experiences of a mindfulness meditation-based stress reduction intervention for combating music performance anxiety - MacCutcheon, Douglas (University of Pretoria, 2022)
Mini Dissertation (MMus (Performance))--University of Pretoria, 2022.